Barley varieties registered in the Slovak Republic after the harvest 2022: ENG/CZ - Psota, Vratislav; Svorad, Marián; Musilová, Markéta; Boško, Rastislav (KVASNY PRUMYSL, 2023)
The study presents the results of technological quality and agronomic characteristics of the spring barley LG Flamenco and winter barley Sonja. These varieties have passed three-year trials within the state varietal trials of the Slovak Republic. At the optimum nitrogen content in unmalted grain, the LG Flamenco variety showed an extract content of 83.2% and the Sonja variety 81.4%. The diastatic power was at the optimum level for both varieties (316 and 411 WK un.). The Kolbach index was at the optimum level (48.3%) for LG Flamenco and 39.6% for Sonja. In the LG Flamenco variety, cell wall degradation was given by a friability value of 88% and a β-glucan content of 192 mg/l. The friability value for the variety Sonja was 82% and the β-glucan content was 193 mg/l. The quality (apparent final attenuation) of the sweet wort was satisfactory for both varieties (81.0%).